Fuelwood consumption and deforestation in African countries - Dennis, Anderson; Fishwork, Robert (Washington, 1984)
The paper reviews recent reports on the level and growth of fuelvood consumption in Africa, and on the ecological, economic and possible micro-climatic effects of deforestation. It then reviews the economic and operational aspects of policies open to governments (1) to encourage fuelwood conservation, (ii) to facilitate the substitution of commercial energy for fuelwood, where desirable on grounds of relative costs, (111) in developing the traditional functions of the forestry services in maintaining the forest reserves and undertaking plantings in watersheds and shelterbelts, and (iv) in promoting the practice of agro-forestry, i.e. the planting and maintenance of trees in copses and around farms by the farm families themselves. All four are important, but it is argued that (iv) offers considerable promise in terms of increased planting rates, low budgetary requirements, ecological benefits and good economic and financial rates of return. The importance of the 'policy environment for the success of each is also discussed, as are the various research, education, training and other requirements of (iv).
Keywords: Fuelwood industry Africa